Static anti-windup compensator based on BMI optimisation for discrete-time systems with directional change in controls avoidance - Horla, Dariusz (Bulletin of the Polish Academy of Sciences Technical Sciences, 2024)
In the paper, a design method of a static anti-windup compensator for systems with input saturations is proposed. First, an anti-windup controller is presented for system with cut-off saturations, and, secondly, the design problem of the compensator is presented to be a non-convex optimization problem easily solved using bilinear matrix inequalities formulation. This approach guarantees stability of the closed-loop system against saturation nonlinearities and optimizes the robust control performance while the saturation is active.